Knowledge and skills partnerships in youth justice - Price, Jayne; Creaney, Sean (Routledge, 2025)
"Providing in-depth insight into different types of knowledge and skills partnerships in youth justice, this book illustrates the importance of collaborative working between academics and professionals, drawing on empirical research and practice examples to present expert analysis of knowledge/evidence production and utilization in youth justice. Original and cutting edge, the focus of this edited collection is on different forms of knowledge exchange (transfer) between professionals and academics in the youth justice context. Authored by experts in the field, each chapter presents a series of case studies showcasing the application of theory/evidence to practice, and shedding light on the challenges professionals experience when seeking to understand complex theory and 'make sense' of the vast array of empirical data. Knowledge and Skills Partnerships in Youth Justice will appeal to students researching youth justice and criminal justice systems. The book will also be useful for practitioners of youth justice, as well as policymakers"--